LaGeR: Lenguaje para descripción de gestos bidimensionales y tridimensionales. - Odio-Vivi, Andrés (Instituto Tecnológico de Costa Rica, 2015)
The recent boom in virtual reality is fostering the proliferation of gestural input devices such as the Razer Hydra, the Leap Motion 3D Controller, and the Microsoft Kinect. This hinders the work of researchers and application developers, since they must write their programs using a diﬀerent API for each device. The main goal of this research was to deﬁne and implement a language for the representation and interpretation of bidimensional and tridimensional gestures. Through it, developers will be able to use the language to deﬁne gestures to be detected regardless of the device or the underlying APIs. We investigated diﬀerent ways of representing and recognizing gestures, and then created LaGeR — Language for Gesture Representation. In order to test its feasibility, we wrote a set of software tools and libraries for converting sensor movements into LaGeR strings, recognizing them as gestures, visualizing them, and notifying subscribed programs of their detection. We also created a test program that uses said framework to control the Google Chrome web browser through gestures. We tested the application with users and showed that LaGeR is a useful and eﬀective language for representing gestures and developing gesture-based applications
Proyecto de Graduación (Maestría en Computación) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Computación, 2015.
Keywords: Programación; Lenguajes de programación; Realidad virtual; Costos